Studi Penurunan Kadar COD (Chemical Oxygen Demand) dan TSS (Total Suspended Solid) Menggunakan Ferri Klorida (Fecl3) pada Limbah Cair Industri Pembuatan Tahu - Kartika Dian Pertiwi; Yuliaji Siswanto; Ita Puji Lestari (Universitas Ngudi Waluyo, 2024)
The tofu industry is a business established to develop activities in the food sector that have positive and negative impacts on the environment. The source of tofu industrial waste in Semarang comes from several process stages which produce average values ​​of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solid (TSS) which are very far from the thresholds determined by industrial wastewater quality standards. tofu by the government according to Central Java Provincial Regulation No.5 of 2012. The aim of this research is to determine the effectiveness of ferric chloride (FeCl3) as a coagulant in the wastewater treatment process of the tofu making industry with test parameters COD and TSS. This type of research is a quasi-experiment. The research design used was a pretest-posttest with control group design. The samples in this research were 35 samples of tofu liquid waste produced from the tofu industry in Gogik Village, East Ungaran District, Semarang Regency. The results of this research show that there is a difference in the Chemical Oxygen Demand (COD) levels of tofu waste before and after the addition of FeCl3 coagulant with a significance value of 0.016 or a probability below 0.05 (0.016 < 0.05), with the most effective dose being 40 gr/L waste water, There is a difference in the Total Suspended Solid (TSS) levels of tofu waste before and after the addition of FeCl3 coagulant with a significance value of 0.001 or the probability is below 0.05 (0.001 < 0.05). the probability is below 0.05 (0.001 < 0.05). ABSTRAK Industri tahu merupakan usaha yang didirikan dalam rangka pengembangan kegiatan di bidang pangan yang mempunyai dampak positif dan negatif bagi lingkungan. Sumber limbah industri tahu di Semarang berasal dari beberapa tahapan proses yang menghasilkan nilai rata-rata Biochemichal Oxygen deman (BOD), Chemical Oxygen Demand (COD), dan Total Suspenden Solid (TSS) sangat jauh dari ambang batas yang ditentukan baku mutu air limbah industri tahu oleh pemerintah menurut Perda Provinsi Jawa Tengah No.5 Tahun 2012. Tujuan penelitian ini adalah untuk mengetahui efektivitas ferri klorida (FeCl3) sebagai koagulan dalam proses pengolahan air limbah industri pebuatan tahu dengan parameter uji COD dan TSS. Jenis penelitian ini adalah eksperimen semu. Rancangan penelitian yang digunakan adalah pretest-postest with control group design. Sampel dalam penelitian ini adalah limbah cair tahu yang dihasilkan dari industri tahu di Desa Gogik, Kecamatan Ungaran Timur, Kabupaten Semarang sebanyak 35 sampel. Hasil dari penelitian ini menunjukkan Ada perbedaan kadar Chemical Oxygen Demand (COD) limbah tahu sebelum dan setelah diberikan penambahan koagulan FeCl3 dengan nilai signifikansi 0,016 atau probabilitasnya dibawah 0,05 ( 0,016 < 0,05 ), dengan dosis paling efektif adalah 40 gr/L air limbah, Ada perbedaan kadar Total Suspended Solid (TSS) limbah tahu sebelum dan setelah diberikan penambahan koagulan FeCl3 dengan nilai signifikansi 0,001 atau probabilitasnya dibawah 0,05 ( 0,001 < 0,05 ). probabilitasnya dibawah 0,05 ( 0,001 < 0,05 ).